Theatre minus physical coexistence – a glimpse into theatrical experimentations in Greece during the pandemic. Issue 1 (2nd January 2022) - Liodaki, Danai; Velegrakis, Giorgos
ABSTRACT: The peculiar circumstances of the COVID-19 pandemic inevitably lessened the possibilities of physical proximity while a multitude of functions and activities were transferred to the digital space, theatre included. As a result, many cultural institutions, theatrical organisations and theatre artists were forced to experiment with theatrical practices that did not involve the element of physical coexistence between audience and performers. This paper attempts to investigate the outcome of a theatrical event that lacks a shared physical space between the performers and the audience, by focusing on five typical examples of such theatrical experimentations in mid-pandemic Greece. The five experimentations are researched under three analytical categories, namely 'space', 'time' and 'other space and time'. The main questions addressed are what is new, what is transformed and what is missing when theatrical practices are forced to transfer to the digital world. The focus is on both the performers and the audiences, therefore semi-constructed interviews – with actors, directors and audience members – were held. Finally, conclusion is reached regarding those transfers and the transformative power of the theatrical praxis in physical and digital environments.